Epidemiology and clinical features of intestinal protozoan infections detected by Real-time PCR in non-native children within an Italian tertiary care children's hospital: A cross-sectional study. Issue 43 (September 2021) - Venturini, Elisabetta; Scarso, Salvatore; Prelazzi, Ginevra Alfa; Niccolai, Claudia; Bianchi, Leila; Montagnani, Carlotta; Lapini, Manuela; Chiappini, Elena; Antonelli, Alberto; Rossolini, Gian Maria; Galli, Luisa
Abstract: Background: Enteric parasite infections are underestimated due to the limited sensitivity and specificity of microscopy, which remains the diagnostic gold standard in routine clinical practice. This could be a major problem in high-income countries, where the burden of parasitic diseases is low. In recent years, Multiplex Real-Time polymerase chain reaction (RT-PCR) based methods have been implemented. Therefore, the aim of this study was to evaluate the prevalence of four enteric protozoan species detected by RT-PCR in non-native children in Italy, and to describe their clinical characteristics. Methods: Adopted and immigrant children, evaluated for migration health assessment between 2017 and 2020 in a tertiary care children's hospital in Italy, were enrolled. Molecular analysis for Giardia lamblia, Dientamoeba fragilis, Blastocystis hominis, and Entamoeba histolytica, was conducted by in-house RT-PCR. Results: Overall, 209 children were enrolled and 70% of them resulted positive by RT-PCR for at least one enteric parasite. B. hominis (47.8%) was the most commonly identified protozoa, followed by D. fragilis (44.5%). Co-infections with multiple pathogens were detected in 35.4% of the samples. Almost 80% of parasite-positive children were asymptomatic and the most common symptom was flatulence (60.7% of symptomatic children). Eosinophils were significantly increased in RT-PCR positive children compared to the negative ones and children with D. fragilis presented the highest eosinophils count. Conclusions: The In-house Multiplex RT-PCR assay provides a valid molecular detection system for selected enteric parasites. This novel and accurate diagnostic method can help in increasing the detection rate of parasite infection, especially in high-risk population. Highlights: Over 2/3 of enrolled children resulted positive for one or more parasites. Almost 80% of positive screened children were asymptomatic and the most common symptom was flatulence. The presence of co-infection was detected in almost one third of positive screened cases. Low hemoglobin and ferritin levels were found in children with G. lamblia . Children with D. fragilis had a higher eosinophils count compared to other protozoa.